Cortical and subcortical responses to high and low effective placebo treatments. - Geuter, S; Eippert, F; Hindi Attar, C; Büchel, C (2013)
The effectiveness of placebo treatments depends on the recipient's expectations, which are at least in part shaped by previous experiences. Thus, positive past experience together with an accordant verbal instruction should enhance outcome expectations and subsequently lead to higher placebo efficacy. This should be reflected in subjective valuation reports and in activation of placebo-related brain structures. We tested this hypothesis in a functional magnetic resonance imaging study, where subjects experienced different levels of pain relief and conforming information about price levels for two placebo treatments during a manipulation phase, thereby establishing a weak and a strong placebo. As expected, both placebos led to a significant pain relief and the strong placebo induced better analgesic efficacy. Individual placebo value estimates reflected treatment efficacy, i.e. subjects were willing to pay more money for the strong placebo even though pain stimulation was completed at this time. On the neural level, placebo effects were associated with activation of the rostral anterior cingulate cortex, the anterior insula, and the ventral striatum and deactivations in the thalamus and secondary somatosensory cortex. However, only placebo-related responses in rostral anterior cingulate cortex were consistent across both the anticipation of painful stimuli and their actual administration. Most importantly, rostral anterior cingulate cortex responses were higher for the strong placebo, thus mirroring the behavioral effects. These results directly link placebo analgesia to anticipatory activity in the ventral striatum, a region involved in reward processing, and highlight the role of the rostral anterior cingulate cortex, as its activity consistently scaled with increasing analgesic efficacy.